Emerging sectors in rural development - Viaene, Jacques; De Steur, Hans (Acta Agraria Debreceniensis, 2012)
This paper focuses on the innovativeness of rural economy and in particular on the way rural entrepreneurs in endogenous and exogenous sectors make use of their rural environment. building upon the sustainable innovation framework, key strategies for rural development are formulated. the described data refers to the rural innova region (10 rural eu regions). The results show that rural innovation is essentially a process of valorising endogenous potentials by connecting them with exogenous assets.